Exposures of olivine‐rich rocks in the vicinity of Ares Vallis: Implications for Noachian and Hesperian volcanism. Issue 5 (9th May 2013) - Wilson, J. H.; Mustard, J. F.
ABSTRACT: [1] The igneous evolution of Mars is well represented in stratigraphic settings that transition across major time stratigraphic boundaries. Here we analyze in detail the morphology and composition, determined through visible–near‐infrared spectroscopy, of igneous volcanic terrains in Ares Vallis, Mars. Upland plateau units with crater‐filling volcanic plains are of Noachian age; smooth units to the west and north of the mouth of Ares Vallis have been mapped as Hesperian in age. The age and origin of the units that comprise the floor of Ares Vallis, connecting the upland plateau units and the smooth units to the west and north of the mouth of Ares Vallis, is less certain due to the small area available for crater counting. The mafic mineral compositions of these units are well resolved with OMEGA (Observatoire pour la Mineralogie, l'Eau, les Glaces et l'Activité) and CRISM (Compact Reconnaissance Imaging Spectrometer for Mars) data. The data show that the Noachian volcanic units are distinctly olivine‐rich, while the plains units to the west and the floor of Ares Vallis volcanics show diagnostic absorptions of olivine‐pyroxene, typical of Hesperian volcanics elsewhere on Mars. Based on these findings, we propose there has been a change in the temperature and/or degree of partial melting in the mantle over time for this region of Mars. Key Points: Noachian and Hesperian volcanics identified in close stratigraphic proximity VNIR spectroscopy is used to characterize Noachian and Hesperian volcanics Differences in spectral character can be refined from previous studies